2010
DOI: 10.1007/s00405-010-1400-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction model for hearing outcome in patients with idiopathic sudden sensorineural hearing loss

Abstract: The aim of this study is to develop a regression model for predicting hearing outcome in patients with idiopathic sudden sensorineural hearing loss (ISSNHL). A total of 174 consecutive patients with ISSNHL (average of the hearing levels at 250, 500, 1,000, 2,000, and 4,000 Hz was ≥40 dB; time from onset to treatment was ≤30 days) were retrospectively analyzed. They received steroid administration (400 mg/day of hydrocortisone sodium succinate followed by tapered doses) in combination with hyperbaric oxygen the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…The association between the subjective perception of vertigo and worse outcome could be demonstrated by several studies [32, 33, 3645]. But, the association between objective calorimetric tests and hearing outcome was only investigated by a few [29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…The association between the subjective perception of vertigo and worse outcome could be demonstrated by several studies [32, 33, 3645]. But, the association between objective calorimetric tests and hearing outcome was only investigated by a few [29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…3D‐FLAIR MRI post‐transtympanic gadolinium injection has contributed to the detection of endolymphatic hydrops in patients with ISNHL and vertigo who had not previously been definitely diagnosed in vivo. Vertigo is considered a factor that compromises the efficiency of treatment in ISNHL 9. In our study, the results of the 3D‐FLAIR MRI after intratympanic gadolinium injection indicates an underlying association between endolymphatic hydrops and vertigo.…”
Section: Discussionmentioning
confidence: 49%
“…Because of the multifactorial etiopathology, a number or different regimens have been used as therapy, including vasodilators, anticoagulants, corticosteroids, vitamins, plasma expander, histamine, antiviral agents, batroxobin, contrast media, stellate ganglion block, hyperbaric oxygen, and carbogen (Suzuki H et al, 2011).…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognomentioning
confidence: 99%
“…The presence of vertigo is one of important prognostic factors for recovery of hearing loss which many studies recommended (Kang D & Wan L, 2005;Suzuki H et al, 2011;Cvorović L et al, 2008). Some studies reported that BPPV in patients with SSHL, representing definitive vestibular damage, was closely related to poor prognosis (Lee NH & Ban JH, 2010).…”
Section: Fig 3 Decision Tree Model Of Important Variables As Prognomentioning
confidence: 99%
See 1 more Smart Citation